7 - Mutual Gains from Hostile Confrontations: Land Boards, Their Clients and ‘Self-allocation’ in Botswana: https://doi.org/10.4314/ad.v34i1.57360 - Onoma, Ato Kwamena (Africa Development, 2009)
This article argues that hostile confrontations between state and societal actors pursuing divergent goals can sometimes end up empowering both. In Botswana, successful efforts by less powerful clients to reclaim the power to allocate land from land boards through various stratagems ended up also strengthening the land boards and also the state. By tricking land boards into legitimizing plots on which they had squatted, clients brought their land interests to the awareness of the land board and contributed to bettering land board records. The better records enable land boards to allocate land and resolve disputes in more in- formed ways. Better records also provide state officials with valuable informa- tion that various state agencies can use to tax, police, plan and implement vari- ous social projects better. In presenting this argument, the article contributes to the state-in-society discourse by showing that we need not limit the possibility of positive sum gains to situations where state and societal actors collaborate to achieve mutual goals.